The Effectiveness of Vibration Reduction Trenches in a Dynamic Replacement Project - Hamidi, Babak; Varaksin, S.; Nikraz, Hamid (The Australian Geomechanical Society and New Zealand Geotechnical Society, 2012)
Umm Al Quwain Marina Phase I Project is located in northern United Arab Emirates. The site is located in an area where the ground consists of 6 to 7 m of very loose heterogeneous saturated silt and silty sand. More than 86,000 m2 of the site has been treated using dynamic replacement. Due to the presence of existing structures in the vicinity of the ground improvement works vibration monitoring and control was implemented. In this paper, initially previous studies on dynamic compaction vibration will be reviewed, then the two cases of vibration monitoring programme for UAQ Marina will be described. First, particle velocities and their associated frequencies were measured at different distances from the pounder’s impact point when no specific measures were implemented. Next, a vibration reduction trench was excavated and the vibration parameters recorded again. The interpretation of the results indicates that the vibration reduction trench has been able to efficiently reduce peak particle velocities to about one half the values when the trench was not installed. This study demonstrates that simple methods such as constructing vibration reduction trenches can be an effective way for controlling vibration damage when existing structures are nearby.